Predictors of birth preparedness among women in Laikipia County, Kenya - Wanjohi, Joseph M.; Wanyoro, Anthony K.; Makunyi, Eliphas G. (International Journal Of Community Medicine And Public Health, 2022)
Background: Maternal complications are the second leading cause of death among women after HIV/AIDS. World Health Organization (WHO) estimates that about 94% of all maternal deaths worldwide occur in developing countries. Evidence shows that birth preparedness; the process of strategizing for normal spontaneous vaginal delivery and anticipating the action plan in an obstetric emergency, reduces maternal mortality. Methods: The study assessed the predictors of birth preparedness among women in Laikipia county, Kenya. It was a mixed method, cross-sectional analytical study conducted among 259 women who had delivered within one year prior to the study. Facilities were selected through simple random sampling, whereas participants were selected through systematic sampling. It was a facility-based study using structured questionnaire and key informant interview guide, and data analysed using Statistical package for the social sciences (SPSS). Results: The level of birth preparedness was 23.2%. Inferential statistical tests showed that education, occupation and income, were statistically significant associated with the level of birth preparedness p<0.05, CI=95%). Logistic regression showed that tertiary education (AOR=8.469), formal employment (AOR=4.898) and, income above Kshs 39,000 (AOR=4.834) had a positive association with birth preparedness. Conclusions: The level of birth preparedness was low in Laikipia County. Woman’s education, occupation and household monthly income were the predictors of birth preparedness.